The Effectiveness of Classroom E-earning in Improving Reading and Writing Skills of Students with Learning Difficulties in the Fourth Grade of Primary School in the City of Doha in the State of Qatar - Almustafa, Ghadeer; Al-Hamidi, Moayad (Dirasat: Educational Sciences, 2022)
Objectives: This study aims to identify the effectiveness of classroom e-learning in improving reading and writing skills of students with learning difficulties in the fourth grade of primary school in the city of Doha in the State of Qatar. The study population consisted of all students of learning disability in the city of Doha, for the second semester 2020/2021. The study sample consisted of (31) students who were randomly selected. Methods: An experimental method was used in the study, where an achievement test in reading and writing consisting of (60) items was used, after verifying its validity and reliability. Results: The results showed that there are statistically significant differences at the significance level of α≤ 0.05 between the mean scores of the students and in favor of the post-test in reading and writing skills (t = 13.19). The results also showed that there were no statistically significant differences at a significance level of α≤ 0.05 between the mean scores of students in reading and writing skills according to gender. Conclusions: The study recommends employing educational technology in teaching students with disabilities, especially students with learning difficulties and adopting educational technology methods in developing curricula to meet the needs of students with learning difficulties.